Writing board coating, preparation method thereof and writing board

By using microcrystalline cellulose-acrylate modified alkyd resins and epoxy resins and titanium dioxide-zirconium dioxide-acrylate polymers in the writing board coating, a coating with high adhesion and easy cleaning is solved. In the technology, the poor adhesion and insufficient cleaning performance of the writing board coating have extended the service life of the writing board and improved the user experience.

CN119119836AInactive Publication Date: 2024-12-13SHENZHEN HONGHE INNOVATION INFORMATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411284296.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing writing board coating has poor adhesion to the substrate, short service life, and insufficient cleaning and wiping performance, which affects the beauty and user experience of the blackboard.

Method used

Use composite writing board coating coatings, including primer coatings and topcoat coatings, use microcrystalline cellulose-acrylate modified alkyd resins and epoxy resins in primer coatings, and add titanium dioxide-zirconium dioxide to topcoat coatings. -Acrylate polymers, through the combination of these components, form highly meshed structures and hydrophobic coatings, improving adhesion and mechanical properties.

Benefits of technology

It significantly improves the adhesion and service life of the writing board coating, enhances the wipeability and weather resistance of the writing board, makes the writing board easy to clean and maintain, and improves the writing experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119836A_ABST
    Figure CN119119836A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, and provides a writing board coating which is arranged on a writing board main body and comprises a base coating and a top coating, microcrystalline cellulose-acrylate modified alkyd resin and first epoxy resin are used as film forming substances in the base coating, and the first epoxy resin and the second epoxy resin are used as film forming substances in the top coating. Acrylate and second epoxy resin are used as film-forming substances in the top-coat paint, and a titanium dioxide-zirconium dioxide-acrylate polymer is added into the top-coat paint. According to the writing board coating provided by the invention, the prime coating and the top coating are compounded, the prime coating endows the coating with excellent adhesive force, and the top coating endows the coating with an excellent self-cleaning function, so that the coating is easy to wipe, the prime coating is combined with the top coating, and the self-cleaning effect is good. The writing board coating with high durability, adhesive force and hydrophobicity can be obtained, and good writing experience is brought.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of coatings, and in particular relates to a writing board coating, a preparation method thereof, and a writing board. Background Art

[0002] With the growing demand for education and commercial display, the performance requirements of blackboards as a traditional writing and display tool are also increasing. There are many types of blackboard substrates on the market, including but not limited to metal, wood, plastic, etc. These substrates achieve writing functions through coating.

[0003] However, existing coating materials have relatively weak adsorption to substrates, resulting in a short service life of the coating and difficulty in being applied to multiple substrates at the same time, which limits its scope of application.

[0004] In addition, the existing blackboard coating has many deficiencies in terms of cleaning and wiping. Ordinary traditional chalks are easy to leave dust and scratches on the coating surface after wiping, affecting the appearance and service life of the blackboard. The new water-soluble chalks are difficult to wipe off during wiping, and will leave traces of oil and wax after wiping, which brings inconvenience to users and further affects the cleanliness and writing experience of the blackboard. Summary of the invention

[0005] The purpose of the present application is to provide a writing board coating and a preparation method thereof, aiming to solve the problem that the existing writing board coating has poor adhesion to the substrate and the cleanliness and wiping properties of the formed coating are insufficient.

[0006] Another object of the present application is to provide a writing board to solve the problem that the existing writing boards are difficult to wipe and have a short service life.

[0007] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0008] In a first aspect, the present application provides a writing board coating, which is disposed on a writing board body, wherein the coating of the writing board coating comprises a primer coating and a top coating; wherein:

[0009] The primer coating comprises the following components in the following parts by weight:

[0010]

[0011] The topcoat coating comprises the following components in the following parts by weight:

[0012]

[0013] In a second aspect, the present application provides a method for preparing a writing board coating, comprising the following steps:

[0014] Provide various raw materials according to the coating material of the writing board coating provided in the first aspect;

[0015] The microcrystalline cellulose-acrylate modified alkyd resin, the first epoxy resin, the first pigment, the first organic solvent, the first film-forming aid, the first dispersant, the first leveling agent, the first thickener and the drying agent in the formula of the primer coating are mixed to obtain the primer coating;

[0016] Mixing titanium dioxide-zirconium dioxide-acrylate polymer, acrylate, a second epoxy resin, a second pigment, a second organic solvent, a second dispersant, a second film-forming aid, a second leveling agent, and a second thickener in a formula of a top coating to obtain a top coating;

[0017] The primer and topcoat are sequentially applied on the surface of the writing board to form a writing board coating.

[0018] In a third aspect, the present application provides a writing board, comprising a writing board substrate and a coating disposed on the surface of the writing board substrate, wherein the coating comprises the writing board coating provided in the first aspect or the writing board coating prepared by the preparation method provided in the second aspect.

[0019] The writing board coating provided in the first aspect of the present application adopts a coating comprising a compounded primer coating and a top coating, wherein the primer coating comprises microcrystalline cellulose-acrylate modified alkyd resin and a first epoxy resin as main film-forming substances, and the alkyd resin is modified by microcrystalline cellulose and acrylate at the same time, which not only significantly improves the adhesion and versatility of the alkyd resin substrate, but also effectively improves the compatibility between the alkyd resin and the first epoxy resin, thereby forming a highly networked structure in combination with other components to form a primer coating that is not easy to age and has high adhesion; titanium dioxide-zirconium dioxide-acrylate polymer is added to the top coating, and the surface roughness of zirconium dioxide can be effectively increased by combining titanium dioxide with zirconium dioxide to form a coating with better hydrophobicity, and the presence of acrylate not only improves the compatibility between titanium dioxide, zirconium dioxide and the film-forming substance, but also makes it difficult for titanium dioxide and zirconium dioxide to agglomerate, so that the mechanical properties of the coating are effectively improved, and the coating exhibits good weather resistance and easy cleaning properties.

[0020] The second aspect of the present application provides a method for preparing a writing board coating. The raw materials of each component are mixed according to the components and proportions contained in the coating of the writing board coating of the present application, so that the raw material components are evenly dispersed, and then the coating can effectively prepare a writing board coating with excellent adsorption, high wipeability, and easy cleaning and maintenance. In addition, the preparation method of the writing board coating of the present application has simple process conditions, is reliable and controllable, and can ensure that the prepared writing board coating has stable performance and high efficiency, and is suitable for industrial application and promotion.

[0021] The writing board provided in the third aspect of the present application is provided with the writing board coating provided by the present application or the writing board coating prepared by the preparation method provided by the present application. The writing board coating has excellent adhesion to the substrate, thereby effectively improving the service life of the writing board, and giving the writing board good erasability and weather resistance, making the writing board easy to clean and maintain, effectively enhancing the writing experience. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0023] Figure 1 It is a schematic diagram of the structure of the writing board provided in the embodiment of the present application.

[0024] Among them, the reference numerals in the figure are:

[0025] 100. Writing board;

[0026] 10. Base material, 20. Base coating, 30. Top coating. DETAILED DESCRIPTION

[0027] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0028] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0029] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0030] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0031] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0032] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0033] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0034] In the present application, "perfluorocarbon chain" refers to a long chain structure composed of carbon atoms and fluorine atoms, in which all hydrogen atoms on the carbon atoms are replaced by fluorine atoms.

[0035] In the present application, "double bond" refers to a carbon-carbon double bond (-C=C-), which is a covalent bond formed by two carbon atoms being bonded together through two pairs of shared electrons.

[0036] The term "carbon-oxygen bond" refers to a chemical bond formed between a carbon atom and an oxygen atom, and in the present application, refers to a carbon-oxygen single bond (-CO-).

[0037] The term "methylene" refers to a group of a carbon atom linked to two hydrogen atoms, ie, -CH2-.

[0038] In a first aspect, an embodiment of the present application provides a writing board coating, wherein the coating of the writing board coating comprises a primer coating and a top coating; wherein:

[0039] The primer coating comprises the following components in the following parts by weight:

[0040]

[0041] The topcoat coating comprises the following components in the following parts by weight:

[0042]

[0043] In the technical scheme of the application, the primer coating uses microcrystalline cellulose-acrylate modified alkyd resin and the first epoxy resin as the main film-forming substances. The alkyd resin is modified by microcrystalline cellulose and acrylate at the same time, which not only significantly improves the adhesion and versatility of the alkyd resin to the substrate, but also effectively improves the compatibility of the alkyd resin with the first epoxy resin. As a result, the film-forming substance can easily form a more uniform, dense coating with a wider range of substrate adaptability, and give the coating a higher adhesion. The first pigment and the first film-forming aid can enhance the mechanical properties and weather resistance of the coating. The first dispersant is conducive to the film-forming substance, the first pigment and other components to form a uniform and stable system, so that the coating is not easy to agglomerate and precipitate. In this way, through the synergistic enhancement between the microcrystalline cellulose-acrylate modified alkyd resin, the first epoxy resin and other components, a primer coating with excellent adhesion, high mechanical properties and better versatility can be obtained.

[0044] In the technical solution of the application, titanium dioxide-zirconium dioxide-acrylate polymer is added to the topcoat. Titanium dioxide and zirconium dioxide have excellent mechanical properties. The combination of titanium dioxide and zirconium dioxide can effectively increase the surface roughness of zirconium dioxide, forming a more hydrophobic and easy-to-clean coating. The presence of acrylate not only makes the compatibility between titanium dioxide, zirconium dioxide and the film-forming substance better, but also makes it difficult for titanium dioxide and zirconium dioxide to agglomerate, thus forming a uniform, dense and weather-resistant coating, which effectively improves the mechanical properties and easy-to-clean property of the coating. Therefore, with the second acrylate and the second epoxy resin as the film-forming substance, combined with titanium dioxide-zirconium dioxide-acrylate polymer, the second pigment filler, the second dispersant, the second film-forming aid and other components, it is easy to obtain a uniform and stable coating, forming a writing board coating with anti-fouling properties, easy to clean and easy to wipe.

[0045] In the embodiment of the present application, a primer coating and a top coating are compounded. The primer coating gives the writing board coating excellent adhesion, providing stable and reliable support for the entire writing board coating system; the top coating gives the writing board coating excellent self-cleaning function, making the writing board coating easy to wipe. In this way, the primer coating and the top coating are combined, and the two complement each other and can be strongly adhered to common substrates such as metal plates, glass plates, and ceramic plates. After coating, a writing board coating with high hardness, good wear resistance, and corrosion resistance is formed on the surface of the substrate, which forms a covering and protective effect on the substrate, which is beneficial to improving the overall service life. At the same time, the writing board coating formed has excellent easy-to-wipe and easy-to-clean effects, and also brings a better writing experience.

[0046] For example, in the primer coating, the weight percentage of the microcrystalline cellulose-acrylate modified alkyd resin can be 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 78 parts, 80 parts, etc., which are typical but non-limiting values.

[0047] For example, in the primer coating, the weight percentage of the first epoxy resin can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc., which are typical but non-limiting values.

[0048] For example, in the primer coating, the weight percentage of the first pigment can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, etc., which are typical but non-limiting values.

[0049] For example, in the primer coating, the weight percentage of the first organic solvent may be 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, etc., which are typical but non-limiting values.

[0050] For example, in the primer coating, the weight percentage of the first film-forming aid can be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, etc., which are typical but non-limiting values.

[0051] For example, in the primer coating, the weight percentage of the first dispersant can be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, etc., which are typical but non-limiting values.

[0052] For example, in the primer coating, the weight percentage of the first leveling agent can be 0.1 part, 0.3 part, 0.5 part, 0.7 part, 0.9 part, 1 part, etc., which are typical but non-limiting values.

[0053] For example, in the primer coating, the weight percentage of the first thickener can be 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, etc., which are typical but non-limiting values.

[0054] For example, in the primer coating, the weight percentage of the catalyst may be 0.4 parts, 0.5 parts, 0.6 parts, etc., which are typical but non-limiting values.

[0055] For example, in the topcoat, the weight percentage of the titanium dioxide-zirconium dioxide-acrylate polymer can be 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, etc., which are typical but non-limiting values.

[0056] For example, in the topcoat, the weight percentage of the acrylate may be 45 parts, 47 parts, 50 parts, 52 parts, 55 parts, etc., which are typical but non-limiting values.

[0057] For example, in the topcoat, the weight percentage of the second epoxy resin can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc., which are typical but non-limiting values.

[0058] For example, in the topcoat, the weight percentage of the second pigment can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, etc., which are typical but non-limiting values.

[0059] For example, in the topcoat coating, the weight percentage of the second organic solvent may be 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, etc., which are typical but non-limiting values.

[0060] For example, in the topcoat, the weight percentage of the second film-forming aid can be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, etc., which are typical but non-limiting values.

[0061] For example, in the topcoat coating, the weight percentage of the second dispersant can be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, etc., which are typical but non-limiting values.

[0062] For example, in the topcoat, the weight percentage of the second leveling agent can be 0.1 part, 0.3 part, 0.5 part, 0.7 part, 0.9 part, 1 part, etc., which are typical but non-limiting values.

[0063] For example, in the topcoat, the weight percentage of the second thickener can be 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, etc., which are typical but non-limiting values.

[0064] In some embodiments, the microcrystalline cellulose-acrylate modified alkyd resin comprises: an alkyd resin and microcrystalline cellulose, and the alkyd resin and the microcrystalline cellulose are connected via acrylate.

[0065] Microcrystalline cellulose-acrylate modified alkyd resin connects microcrystalline cellulose, acrylate and alkyd resin through acrylate, which easily forms a highly networked structure, giving the coating higher adsorption, versatility and mechanical properties, and also has good compatibility with the first epoxy resin and other primer components, which has an additive improvement effect on improving the adhesion and mechanical properties of the coating.

[0066] In some embodiments, the alkyd resin and the acrylate are connected via at least one of a double bond and a methylene bond.

[0067] The double bonds in the acrylic monomer can react with the unsaturated double bonds or active methylene groups on the side chains of the alkyd resin molecules, thereby enabling the acrylic ester formed by the acrylic monomer to be connected to the alkyd resin through chemical bonds, that is, introducing acrylic ester side chains into the alkyd resin, which not only improves the compatibility between the alkyd resin and the first epoxy resin, but also facilitates the formation of a dense and highly adhesive coating through network cross-linking.

[0068] In some embodiments, the microcrystalline cellulose and the acrylate are connected via at least one chemical bond selected from the group consisting of a double bond and a carbon-oxygen bond.

[0069] The free hydroxyl groups in the microcrystalline cellulose combine with the double bonds and carbon-oxygen bonds in the acrylate, thereby allowing the acrylate to be grafted into the microcrystalline cellulose to form side chains.

[0070] Connecting acrylate and alkyd resin through chemical bonds means that acrylate is grafted onto the side chain of alkyd resin. Therefore, connecting microcrystalline cellulose and acrylate through chemical bonds means that acrylate is grafted onto microcrystalline cellulose to form side chains. In addition, the randomness of the acrylate grafting position makes a number of acrylate side chains randomly distributed on the microcrystalline cellulose. In this way, microcrystalline cellulose and acrylate are easily interwoven to form a network structure, thereby improving the toughness and hardness of the coating.

[0071] In some embodiments, the mass ratio of alkyd resin to microcrystalline cellulose is 23-27: 1. Exemplarily, the mass ratio of alkyd resin to microcrystalline cellulose can be 23: 1, 24: 1, 25: 1, 26: 1, 27: 1, and other typical but non-limiting values.

[0072] Controlling the mass ratio of alkyd resin to microcrystalline cellulose within the above range is beneficial to increasing the formation of a highly networked structure of the alkyd resin, thereby giving the coating higher adsorption, versatility and mechanical properties.

[0073] In some embodiments, the preparation process of microcrystalline cellulose-acrylate modified alkyd resin is as follows:

[0074] Step A10, hydrolyzing microcrystalline cellulose in a solution system to obtain a cellulose solution;

[0075] Step A20, reacting the cellulose solution and methacrylate in a solution system under the condition of a first initiator to obtain methacrylate-grafted cellulose;

[0076] Step A30, mixing butyl acrylate and alkyd resin, and reacting them in a solution system under the condition of a second initiator to obtain butyl acrylate modified alkyd resin;

[0077] Step A40: Mix the methyl acrylate grafted cellulose and the butyl acrylate modified alkyd resin, and react them in a solution system under the condition of a third initiator to obtain microcrystalline cellulose-acrylate modified alkyd resin.

[0078] In the technical solution of the present application, methacrylate is grafted onto microcrystalline fiber to form a side chain, butyl acrylate is reacted with the side chain of alkyd resin to introduce polyacrylic acid side chains into the alkyd resin, and finally methacrylate-grafted cellulose is reacted with butyl acrylate-modified alkyd resin to perform cross-linking grafting through the double bonds located on the side chains, namely the double bonds contained in butyl acrylate and the double bonds contained in butyl acrylate, respectively, to obtain microcrystalline cellulose-acrylate-modified alkyd resin.

[0079] In some embodiments, in step A10, the microcrystalline cellulose is hydrolyzed in a solution system to obtain a cellulose solution in the following specific process:

[0080] Mix 6-7 parts of microcrystalline cellulose with 75-85 parts of dimethylacetamide, place in an oil bath and heat to 145-155°C, stir at 250rpm-350rpm for 1.5h-2h, then when the temperature of the reaction system drops to 95°C-105°C, add 13-16 parts of aluminum chloride, stir at 150rpm-250rpm and drop to 15°C-35°C, react for 9h-11h to obtain a cellulose solution.

[0081] The purpose of step A10 is to hydrolyze the fixed microcrystalline cellulose to provide a basis for subsequent reactions.

[0082] In some embodiments, in step A20, the cellulose solution and methacrylate are reacted in a solution system under the first initiator condition to obtain methacrylate-grafted cellulose in the following specific process:

[0083] The cellulose solution prepared in step A10 is heated in an oil bath and stirred at 150rpm-250rpm to 68℃-72℃; then 0.5-1 part of the first initiator is added and stirred at 150rpm-250rpm until dissolved to obtain a reaction substrate. The reaction substrate is separated by cooling, and then 95-105 parts of dimethylacetamide are added again, and nitrogen is passed through the sealed solution for 30min-40min, and the solution is heated to 60℃-70℃ in an oil bath, and 40-44 parts of methacrylate are added dropwise under stirring at 140rpm-160rpm, and the reaction is carried out at a constant temperature for 23h-24h to obtain methacrylate-grafted cellulose.

[0084] The purpose of step A20 is to graft methacrylate onto microcrystalline cellulose, that is, to graft methacrylate side chains onto microcrystalline cellulose via double bonds and carbon-oxygen bonds.

[0085] Exemplarily, the first initiator includes, but is not limited to, diisopropylphenol, benzoyl peroxide, azobisisobutyronitrile, and tert-butyl perbenzoate.

[0086] In some embodiments, in step A30, butyl acrylate and alkyd resin are mixed, reacted in a solution system under the condition of a second initiator, and the specific process of obtaining butyl acrylate modified alkyd resin is as follows:

[0087] Mix 0.1-0.3 parts of the second initiator and 18-22 parts of butyl acrylate to obtain a premixed monomer;

[0088] Heat 78-82 parts of alkyd resin to 120-130°C, then drop the premixed monomer into the alkyd resin over 1-2 hours, and keep the temperature for 0.8-1.2 hours after the addition is complete;

[0089] Add 0.5-0.6 parts of the second initiator to the alkyd resin twice, keep it for 50 minutes to 60 minutes after the first addition of the second initiator, and keep it for 1.2 hours to 1.5 hours after the second addition of the second initiator;

[0090] The temperature of the reaction system is cooled to below 50° C., triethylamine is added to adjust the pH of the reaction system to 7.5-8.5, and then 50-60 parts of deionized water are added to dilute it, and the mixture is stirred evenly at 140 rpm-160 rpm to obtain butyl acrylate modified alkyd resin.

[0091] In step A30, the double bond in butyl acrylate reacts with the double bond or methylene group in the alkyd resin, so that butyl acrylate and the alkyd resin undergo graft polymerization, thereby introducing polyacrylic acid side chains into the alkyd resin.

[0092] Exemplarily, the second initiator includes, but is not limited to, diisopropylphenol, benzoyl peroxide, azobisisobutyronitrile, and tert-butyl perbenzoate.

[0093] In some embodiments, in step A40, methacrylate-grafted cellulose is mixed with butyl acrylate-modified alkyd resin, and reacted in a solution system under the condition of a third initiator to obtain microcrystalline cellulose-acrylate-modified alkyd resin. The specific process is as follows:

[0094] Add 1-2 parts of methyl methacrylate grafted cellulose to 7-8 parts of butyl acrylate modified alkyd resin, and stir evenly at 550rpm-700rpm;

[0095] Add 0.1-0.3 parts of the third initiator, react at 90°C-110°C for 22h-24h, cool to 15°C-30°C after the reaction is completed; then add 180-220 parts of ice water and let stand for 5.5h-6.5h, filter, wash with ethanol and dry at 60°C-70°C for 2h-3h to obtain microcrystalline cellulose-acrylate modified alkyd resin.

[0096] Exemplarily, the third initiator includes, but is not limited to, diisopropylphenol, benzoyl peroxide, azobisisobutyronitrile, and tert-butyl perbenzoate.

[0097] In some embodiments, the titanium dioxide-zirconium dioxide-acrylate polymer includes titanium dioxide-zirconium dioxide composite microspheres and polyacrylate, and the titanium dioxide-zirconium dioxide composite microspheres and the polyacrylate are connected by a silane coupling agent.

[0098] The titanium dioxide-zirconium dioxide composite microspheres are combined with acrylates by using a silane coupling agent, which effectively increases the compatibility of the titanium dioxide-zirconium dioxide composite microspheres with film-forming substances such as acrylates and second epoxy resins, is more conducive to exerting the role of the titanium dioxide-zirconium dioxide composite microspheres, and improves the cleanability of the coating.

[0099] In some embodiments, the silane coupling agent includes at least one of a perfluorocarbon chain and a double bond.

[0100] For example, the number of carbon atoms in the perfluorocarbon chain may be 5-20.

[0101] The perfluorocarbon chain in the silane coupling agent not only makes it difficult for the titanium dioxide-zirconium dioxide composite microspheres to agglomerate, thus improving their dispersibility, but also improves the hydrophobicity and oleophobicity of the titanium dioxide-zirconium dioxide-acrylate polymer, thereby significantly improving the anti-fouling and easy-to-clean properties of the coating.

[0102] The double bond in the silane coupling agent means that the silane coupling agent can react with the double bond in the acrylic monomer, so that the titanium dioxide-zirconium dioxide composite microspheres are combined with the acrylic ester formed by the acrylic monomer.

[0103] In some embodiments, the titanium dioxide-zirconium dioxide composite microspheres include zirconium dioxide and titanium dioxide deposited on the surface of zirconium dioxide, and the mass ratio of zirconium dioxide to titanium dioxide is 4-6:0.9-1.5. Exemplarily, the mass ratio of zirconium dioxide to titanium dioxide is 4:0.9, 4:1.2, 4:1.5, 5:1, 6:0.9, 6:1, 6:1.5 and other typical but non-limiting values.

[0104] Titanium dioxide is deposited on the surface of zirconium dioxide, which can increase the surface roughness of zirconium dioxide and reduce the surface energy of zirconium dioxide, thereby effectively improving the hydrophobicity of the coating.

[0105] In some embodiments, the particle size of titanium dioxide is on the nanometer scale.

[0106] In some embodiments, the particle size of zirconium dioxide is in the nanometer range. For example, the particle size of zirconium dioxide is 10 nm to 20 nm.

[0107] In some embodiments, the mass ratio of polyacrylate to titanium dioxide-zirconium dioxide composite microspheres is 5-10:4-6.

[0108] For example, the mass ratio of acrylate to titanium dioxide-zirconium dioxide composite microspheres may be 5:4, 5:5, 5:6, 10:4, 10:5, 10:6, and other typical but non-limiting values.

[0109] In some embodiments, the preparation process of titanium dioxide-zirconium dioxide-acrylate polymer is as follows:

[0110] Step B10, preparing a first solution containing glacial acetic acid and a second solution containing zirconium dioxide and tetrabutyl titanate; adding the second solution to the first solution for reaction, and then calcining to obtain titanium dioxide-zirconium dioxide composite microspheres;

[0111] Step B20, reacting the titanium dioxide-zirconium dioxide composite microspheres with a silane coupling agent to obtain titanium dioxide-zirconium dioxide composite microspheres modified with a silane coupling agent;

[0112] Step B30, reacting titanium dioxide-zirconium dioxide composite microspheres modified by a silane coupling agent, acrylic monomer and a fourth initiator in a solution system to obtain a titanium dioxide-zirconium dioxide-acrylate polymer.

[0113] In the technical solution of the present application, titanium dioxide is first deposited on the surface of zirconium dioxide to form micro-nanostructured microspheres, namely titanium dioxide-zirconium dioxide composite microspheres, and then the micro-nanostructured microspheres are modified using a silane coupling agent. This not only improves the hydrophobicity of the micro-nanostructured microspheres, but also the double bonds contained in the silane coupling agent can be grafted and polymerized with acrylates, so that the titanium dioxide-zirconium dioxide composite microspheres and acrylates form a polymer, and the polymer is easier to disperse in the topcoat, increasing the compatibility with other components, which is more conducive to improving the adhesion, mechanical properties and easy cleaning ability of the coating.

[0114] In some embodiments, in step B10, a first solution containing glacial acetic acid and a second solution containing zirconium dioxide and tetrabutyl titanate are prepared; the second solution is added to the first solution for reaction, and then calcined to obtain titanium dioxide-zirconium dioxide composite microspheres. The specific process is:

[0115] 190-210 parts of anhydrous ethanol, 190-210 parts of deionized water, and 15-25 parts of glacial acetic acid are mixed to form a first solution; 190-210 parts of anhydrous ethanol and 4-6 parts of zirconium dioxide are uniformly dispersed by ultrasonication at 40-50KHz and 300-400W, and then 4-6 parts of tetrabutyl titanate are added to obtain a second solution;

[0116] The second solution is added to the first solution within 0.5h-1h, reacted in an oil heat environment at 180℃-220℃ for 23h-24h, then centrifuged at 1000rpm-1200rpm, washed, and finally calcined at 480℃-500℃ for 2h-2.5h to obtain titanium dioxide-zirconium dioxide composite microspheres.

[0117] In some embodiments, in step B20, the specific process of reacting titanium dioxide-zirconium dioxide composite microspheres with a silane coupling agent to obtain titanium dioxide-zirconium dioxide composite microspheres modified with a silane coupling agent is:

[0118] 290-310 parts of anhydrous ethanol and 290-310 parts of toluene are uniformly mixed, and the pH value is adjusted to 9-10 with aqueous ammonia; then 4-6 parts of titanium dioxide-zirconium dioxide composite microspheres are added, and ultrasonic dispersion is performed at 40-50KHz and 300-400W for 20min-30min;

[0119] Then, 0.9-1.32 parts of silane coupling agent are added, reacted at 50° C.-55° C. for 2.5 h-3 h, filtered, washed with ethanol and distilled water, and dried at 100° C. for 0.5-1 h to obtain titanium dioxide-zirconium dioxide composite microspheres modified with silane coupling agent.

[0120] In step B20, the silane coupling agent undergoes a hydrolysis and condensation reaction with the hydroxyl groups on the surface of the titanium dioxide-zirconium dioxide composite microspheres, so that the silane coupling agent is combined with the titanium dioxide-zirconium dioxide composite microspheres.

[0121] In some embodiments, the silane coupling agent includes a perfluorocarbon chain and a double bond.

[0122] Exemplarily, the silane coupling agent includes a silane coupling agent containing a perfluorocarbon chain and a silane coupling agent containing a double bond.

[0123] The mass ratio of the silane coupling agent containing a perfluorocarbon chain to the silane coupling agent containing a double bond can be 0.8-1.2:0.1-0.12.

[0124] As an example, the silane coupling agent containing a perfluorocarbon chain includes, but is not limited to, 1H,1H,2H,2H-perfluorooctyltriethoxysilane (FAS-13).

[0125] As an example, the double bond-containing silane coupling agent includes, but is not limited to, γ-(methacryloxy)propyltrimethoxysilane (KH-570), vinyltriethoxysilane, acryloxypropyltrimethoxysilane, and methacryloxypropyltriethoxysilane.

[0126] In some embodiments, in step B30, the specific process of reacting the titanium dioxide-zirconium dioxide composite microspheres modified with a silane coupling agent, an acrylic monomer, and a fourth initiator in a solution system to obtain a titanium dioxide-zirconium dioxide-acrylate polymer is as follows:

[0127] Mix 38-42 parts of anhydrous ethanol and 4-6 parts of titanium dioxide-zirconium dioxide composite microspheres modified with a silane coupling agent, perform ultrasonic treatment for 20 min-30 min at 40-50 KHz and 300-400 W, then place in an oil bath environment and heat to 55° C.-60° C. to obtain a mixed solution;

[0128] Mix 5-10 parts of acrylate monomer and 0.1-0.3 parts of the fourth initiator, then add dropwise to the mixed solution within 1h-2h, stir and react at 250rpm-350rpm for 5h-6h to obtain a reactant;

[0129] The reactants are distilled at 80-90°C, cooled to 35-40°C, 1-3 parts of N,N-dimethylethanolamine are added, stirred at 700-800rpm, and finally 20-30mL of distilled water are added to obtain titanium dioxide-zirconium dioxide-acrylate polymer.

[0130] In step B30, the double bonds in the silane coupling agent and the double bonds in the acrylic monomer are opened respectively and then recombined, so that the silane coupling agent is combined with the acrylic ester formed by the polymerization of the acrylic monomer. Since the silane coupling agent is combined with the titanium dioxide-zirconium dioxide composite microspheres at the same time, the titanium dioxide-zirconium dioxide composite microspheres can be composited with the acrylic ester.

[0131] In some embodiments, the acrylate monomers include methacrylate, butyl acrylate, and ethylene acrylic acid in a mass ratio of 1-2:3-6:1-2.

[0132] Exemplarily, the fourth initiator includes, but is not limited to, diisopropylphenol, benzoyl peroxide, azobisisobutyronitrile, and tert-butyl perbenzoate.

[0133] In some embodiments, the first epoxy resin and the second epoxy resin each independently include at least one of LY1564 epoxy resin and bisphenol A epoxy resin.

[0134] The epoxy resins have high bonding strength, which significantly improves the adhesion of the coating to the substrate and the applicability of the substrate.

[0135] In some embodiments, the first organic solvent and the second organic solvent each independently include at least one of n-butyl acetate, isopropyl alcohol, acetone, and ethylene glycol methyl ether.

[0136] These organic solvents have a suitable volatilization rate, thereby giving the coating a higher fluidity and leveling property, and can fully dissolve or disperse other components in the coating to form a coating with a uniform system, moderate viscosity and good storage stability.

[0137] In some embodiments, the first pigment and the second pigment each independently include at least one of calcium carbonate, quartz, barium sulfate and talc.

[0138] These pigments and fillers can improve the storage performance and construction performance of the coating, thereby increasing the mechanical strength, wear resistance and water resistance of the coating.

[0139] In some embodiments, the first film-forming aid and the second film-forming aid each independently include at least one of diethylene glycol butyl ether and acrylic acid series film-forming aids.

[0140] Exemplarily, acrylic acid series film-forming aids include, but are not limited to, propylene glycol methyl ether acetate, dodecyl alcohol ester, ethylene glycol butyl ether acetate, dipropylene glycol methyl ether, and dipropylene glycol butyl ether.

[0141] Diethylene glycol butyl ether has low volatility and good solubility, which helps to improve the fluidity and adhesion of the coating, making the coating more uniform and smooth.

[0142] Acrylic acid series film-forming aids can improve the adhesion and weather resistance of the coating, allowing the coating to better bond with the substrate and increase its service life.

[0143] In some embodiments, the first leveling agent and the second leveling agent independently include at least one of an acrylic leveling agent and a silicone leveling agent.

[0144] Exemplary silicone leveling agents include, but are not limited to, BYK-333, BYK-306, Tego410, and Tego450.

[0145] Exemplary acrylate leveling agents include, but are not limited to, MONENG-1154.

[0146] In some embodiments, the first thickener and the second thickener each independently comprise an associative polyurethane thickener.

[0147] The thickener has good compatibility with other components in the coating, can play a stable thickening role, endow the coating with better fluidity and leveling properties, and easily forms a flat and smooth coating.

[0148] In some embodiments, the catalyst includes, but is not limited to, at least one of a cobalt soap drier and a manganese soap drier.

[0149] Cobalt soap drier has good oxidation catalytic ability, which effectively improves the oxygen absorption rate of unsaturated double bonds in the primer coating, prompting the rapid decomposition of peroxides and generating a large number of free radicals, thereby enabling rapid polymerization and cross-linking of film-forming substances, achieving rapid drying and film formation on the surface.

[0150] Manganese soap drier can effectively catalyze the decomposition of peroxides, accelerate the oxidative polymerization process of the primer coating, and make the coating dry faster.

[0151] A second aspect of the embodiment of the present application provides a method for preparing a writing board coating, comprising the following steps:

[0152] Step S10: providing various raw materials according to the coating material of the writing board coating provided in the first aspect;

[0153] Step S20, mixing the microcrystalline cellulose-acrylate modified alkyd resin, the first epoxy resin, the first pigment, the first organic solvent, the first film-forming aid, the first dispersant, the first leveling agent, the first thickener and the drying agent in the formula of the primer coating to obtain the primer coating;

[0154] Step S30, mixing the titanium dioxide-zirconium dioxide-acrylate polymer, acrylate, the second epoxy resin, the second pigment, the second organic solvent, the second dispersant, the second film-forming aid, the second leveling agent and the second thickener in the top coating formula to obtain the top coating;

[0155] Step S40: applying the primer and topcoat to the surface of the writing board in sequence to form a writing board coating.

[0156] The writing board coating provided in the embodiment of the present application is mixed according to the components and proportions of the coating of the writing board coating of the present application, so that the raw materials are evenly dispersed, and then the primer coating and the topcoat coating are applied to the surface of the writing board in sequence, thereby effectively preparing a writing board coating with excellent adsorption, high wipeability, and easy cleaning and maintenance. In addition, the preparation method of the writing board coating of the present application has simple process conditions, is reliable and controllable, and can ensure that the prepared writing board coating has stable performance and high efficiency, and is suitable for industrial application and promotion.

[0157] In some embodiments, in step S10, various raw materials are provided according to the coating, and the addition amount and type of each raw material are selected as described above and will not be described in detail here.

[0158] In some embodiments, in step S20, the specific process of mixing the microcrystalline cellulose-acrylate modified alkyd resin, the first epoxy resin, the first pigment, the first organic solvent, the first film-forming aid, the first dispersant, the first leveling agent, the first thickener and the drying agent in the primer coating formula is as follows:

[0159] Add microcrystalline cellulose-acrylate modified alkyd resin and the first dispersant to the first organic solvent, and stir at a rotation speed of 350rpm-450rpm for 28min-32min; then add the first epoxy resin and the first pigment and filler, and stir at a rotation speed of 1200rpm-1800rpm for 2.5h-3.5h; finally, add the first leveling agent, the first film-forming aid, the first thickener and the drying agent, and stir at a rotation speed of 800rpm-1200rpm for 25min-35min to obtain a primer coating.

[0160] The prepared primer coating can also be filtered through a 200-300 mesh screen.

[0161] In some embodiments, in step S30, the specific process of mixing the titanium dioxide-zirconium dioxide-acrylate polymer, acrylate, second epoxy resin, second pigment, second organic solvent, second dispersant, second film-forming aid, second leveling agent and second thickener in the topcoat coating formula is as follows:

[0162] Add acrylate and the second dispersant to the second organic solvent, and stir at a rotation speed of 350rpm-450rpm for 28min-32min; then add the second epoxy resin, titanium dioxide-zirconium dioxide-acrylate polymer and the second pigment filler, and stir at a rotation speed of 1200rpm-1800rpm for 2.5h-3h; finally, add the second leveling agent, the second film-forming aid and the second thickener, and stir at a rotation speed of 800rpm-1200rpm for 0.5h-1h to obtain a topcoat.

[0163] The prepared topcoat coating can also be filtered through a 200-300 mesh screen.

[0164] In some embodiments, in step S40, the primer coating and the top coating are sequentially applied to the surface of the writing board to form the writing board coating. The specific process is as follows:

[0165] The primer is applied on at least one surface of the writing board and dried to form a primer coating on the surface of the writing board; the top coating is applied on the primer coating and dried to form a top coating.

[0166] It can be understood that the writing board coating includes a base coating and a top coating disposed on the surface of the base coating.

[0167] A third aspect of an embodiment of the present application provides a writing board, which includes a writing board substrate and a coating arranged on the surface of the writing board substrate, and the coating includes the coating provided in the first aspect or the coating prepared by the preparation method provided in the second aspect.

[0168] The writing board provided in this embodiment is provided with the writing board coating provided by the present application or the writing board coating prepared by the preparation method provided by the present application. The coating has excellent adhesion to the substrate, thereby effectively improving the service life of the writing board, and giving the writing board good erasability and weather resistance, making the writing board easy to clean and maintain, effectively enhancing the writing experience.

[0169] In some embodiments, the writing board includes a substrate and a coating disposed on the surface of the writing board substrate, wherein the coating includes a base coating and a top coating stacked together, and the base coating is disposed between the substrate and the top coating.

[0170] The primer layer is formed by coating with the primer coating material contained in the coating material for the writing board coating provided in the first aspect, and the top coating layer is formed by coating with the top coating coating material contained in the coating material for the writing board coating provided in the first aspect.

[0171] In some embodiments, the process of forming a coating on the surface of a writing board is as follows:

[0172] Apply the primer coating uniformly and continuously on at least one surface of the substrate by roller coating, and dry it at 15° C.-35° C. for 2 h-3 h to form a primer coating on the surface of the substrate;

[0173] The top coating is evenly and continuously rolled on the base coating, and dried at 5°C-35°C for 23h-24h to form a top coating.

[0174] See also Figure 1 The writing board 100 includes a substrate 10 and a coating disposed on the surface of the writing board substrate, wherein the coating includes a base coating 20 and a top coating 30 stacked in layers, and the base coating 20 is located between the substrate 10 and the top coating 30 .

[0175] The present application has no particular limitation on the substrate, as long as the purpose of the present application can be achieved. As an example, the substrate includes but is not limited to metal, wood, bamboo, plastic, glass and other composite materials.

[0176] In some embodiments, the thickness of the primer layer is 20 μm-30 μm. As an example, the thickness of the primer layer can be 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm, etc., which are typical but non-limiting values.

[0177] In some embodiments, the thickness of the topcoat layer is 40 μm-50 μm. As an example, the thickness of the topcoat layer can be 40 μm, 41 μm, 42 μm, 43 μm, 44 μm, 45 μm, 46 μm, 47 μm, 48 μm, 49 μm, 50 μm, etc., which are typical but non-limiting values.

[0178] The following describes the invention in conjunction with specific embodiments.

[0179] Example 1

[0180] This embodiment provides a writing board coating and a preparation method thereof.

[0181] A coating for a writing board coating, the composition of which is shown in Table 1 below.

[0182] Table 1

[0183]

[0184] In Table 1:

[0185] The preparation process of microcrystalline cellulose-acrylate modified alkyd resin is as follows:

[0186] Step A1, hydrolysis of microcrystalline cellulose:

[0187] Mix 6.5 parts of microcrystalline cellulose with 80 parts of dimethylacetamide, place in an oil bath and heat to 150°C, stir at 300 rpm for 2 hours, and then when the temperature of the reaction system drops to 100°C, add 15 parts of aluminum chloride, stir at 200 rpm and drop to 20°C, react for 10 hours to obtain a cellulose solution.

[0188] Step A2, preparing methacrylate grafted cellulose:

[0189] The cellulose solution prepared in step A1 was heated in an oil bath and stirred at 200 rpm to 70°C; then 1 part of diisopropylphenol was added and stirred at 200 rpm until dissolved to obtain a reaction substrate. The reaction substrate was separated by cooling, and then 100 parts of dimethylacetamide was added again, and nitrogen was passed through the sealed chamber for 35 minutes. The solution was heated to 65°C in an oil bath, and 42 parts of methacrylate was added dropwise under stirring at 150 rpm. The reaction was continued at a constant temperature for 24 hours to obtain methacrylate-grafted cellulose.

[0190] Step A3, preparing butyl acrylate modified alkyd resin:

[0191] Mix 0.2 parts of benzoyl peroxide and 20 parts of butyl acrylate to obtain a premixed monomer;

[0192] Add 80 parts of alkyd resin into the reaction bottle, heat it to 130°C, then add the premixed monomer to the alkyd resin dropwise within 2 hours, and keep it for 1 hour; then add 0.2 parts of benzoyl peroxide, keep it for 1 hour, and then add 0.3 parts of benzoyl peroxide, and keep it for 1.5 hours;

[0193] The temperature of the reaction system was cooled to below 50° C., triethylamine was added to adjust the pH of the reaction system to 8, and then 55 parts of deionized water were added to dilute it, and stirred evenly at 150 rpm to obtain butyl acrylate modified alkyd resin.

[0194] Step A4, preparing microcrystalline cellulose-acrylate modified alkyd resin:

[0195] Add 2 parts of methyl methacrylate grafted cellulose to 8 parts of butyl acrylate modified alkyd resin and stir evenly at 600 rpm;

[0196] Then, 0.2 parts of benzoyl peroxide initiator was added, and the reaction was carried out at 100°C for 24 hours. After the reaction was completed, the mixture was cooled to 20°C. Then, 200 parts of ice water was added and the mixture was allowed to stand for 6 hours. The mixture was filtered, washed with ethanol, and dried at 65°C for 2 hours to obtain microcrystalline cellulose-acrylate modified alkyd resin.

[0197] The preparation process of titanium dioxide-zirconium dioxide-acrylate polymer is as follows:

[0198] Step B1, preparing titanium dioxide-zirconium dioxide composite microspheres:

[0199] 200 parts of anhydrous ethanol, 200 parts of deionized water, and 20 parts of glacial acetic acid were mixed to form a first solution; 200 parts of anhydrous ethanol and 5 parts of nano zirconium dioxide powder (particle size of 10-20 nm) were ultrasonically dispersed uniformly under 45KHz and 350W conditions, and then 5 parts of tetrabutyl titanate were added to obtain a second solution;

[0200] The second solution was added to the first solution within 1 hour, reacted at 200°C in an oil-heated environment for 24 hours, then centrifuged at 1200 rpm, washed, and finally calcined at 500°C for 2 hours to obtain titanium dioxide-zirconium dioxide composite microspheres.

[0201] Step B2, preparing titanium dioxide-zirconium dioxide composite microspheres modified by a silane coupling agent:

[0202] 300 parts of anhydrous ethanol and 300 parts of toluene were uniformly mixed, and the pH value was adjusted to 9.5 with aqueous ammonia; then 5 parts of titanium dioxide-zirconium dioxide composite microspheres were added, and ultrasonic dispersion was performed at 45KHz and 350W for 30 minutes;

[0203] Then, 1 part of FAS-13 and 0.1 part of KH-570 were added, reacted at 53°C for 3 hours, filtered, washed with ethanol and distilled water, and dried at 100°C for 1 hour to obtain titanium dioxide-zirconium dioxide composite microspheres modified with a silane coupling agent.

[0204] Step B3, preparing titanium dioxide-zirconium dioxide-acrylate polymer:

[0205] 40 parts of anhydrous ethanol and 5 parts of titanium dioxide-zirconium dioxide composite microspheres modified with a silane coupling agent were mixed, ultrasonically treated for 25 minutes at 45 kHz and 350 W, and then placed in an oil bath environment and heated to 60° C. to obtain a mixed solution;

[0206] 2 parts of methacrylate, 4 parts of butyl acrylate, 1 part of ethylene acrylic acid and 0.2 parts of azobisisobutyronitrile were mixed, and then added dropwise to the mixed solution within 2 hours, and stirred at 300 rpm for 6 hours to obtain a reactant;

[0207] The reactants were distilled at 90° C., cooled to 35° C., 3 parts of N,N-dimethylethanolamine were added, stirred at 800 rpm, and finally 20 mL of distilled water were added to obtain titanium dioxide-zirconium dioxide-acrylate polymer.

[0208] A method for preparing a writing board coating comprises the following steps:

[0209] Step S1, providing various raw materials for coating according to Table 1 of Example 1.

[0210] Step S2, adding microcrystalline cellulose-acrylate modified alkyd resin and the first dispersant to the first organic solvent, stirring at a rotation speed of 400 rpm for 30 minutes; then adding the first epoxy resin and the first pigment filler, stirring at a rotation speed of 1600 rpm for 3 hours; finally adding the first leveling agent, the first film-forming aid, the first thickener and the drying agent, stirring at a rotation speed of 1000 rpm for 30 minutes, and finally filtering with a 250-mesh sieve to obtain a primer coating.

[0211] Step S3, adding acrylate and the second dispersant to the second organic solvent, stirring for 30 minutes at a rotation speed of 400 rpm; then adding the second epoxy resin, titanium dioxide-zirconium dioxide-acrylate polymer and the second pigment filler, stirring for 3 hours at a rotation speed of 1600 rpm; finally adding the second leveling agent, the second film-forming aid and the second thickener, stirring for 0.5 hours at a rotation speed of 1000 rpm, and finally filtering with a 250-mesh sieve to obtain a topcoat.

[0212] Step S4, continuously roll-coat the primer coating on the surface of the writing board, and dry it naturally for 2 hours to form a primer coating; then evenly and continuously roll-coat the top coating on the primer coating, and dry it naturally for 24 hours to form a top coating to obtain a writing board coating.

[0213] The substrates of the writing board are electrogalvanized thin steel sheet (SECC), glass and ceramic.

[0214] Example 2

[0215] This embodiment provides a writing board coating and a preparation method thereof.

[0216] A coating for a writing board coating, which differs from Example 1 in terms of raw material composition and mass fraction, as shown in Table 2 below.

[0217] Table 2

[0218]

[0219]

[0220] Example 3

[0221] This embodiment provides a writing board coating and a preparation method thereof.

[0222] A coating for a writing board coating, which differs from Example 1 in terms of raw material composition and mass fraction, as shown in Table 3 below.

[0223] Table 3

[0224]

[0225] Comparative Example 1

[0226] This comparative example provides a writing board coating, which is different from the coating of Example 2 in that the microcrystalline cellulose-acrylate modified alkyd resin is replaced by an alkyd resin.

[0227] Comparative Example 2

[0228] This comparative example provides a writing board coating, which is different from the coating of Example 2 in that the microcrystalline cellulose-acrylate-modified alkyd resin is replaced by acrylate.

[0229] Comparative Example 3

[0230] This comparative example provides a writing board coating, which is different from the coating of Example 2 in that the titanium dioxide-zirconium dioxide-acrylate polymer is replaced by a mixture of titanium dioxide and zirconium dioxide.

[0231] Performance Testing:

[0232] The performance of the writing board coatings provided in Examples 1-3 and Comparative Examples 1-3 of the present application was tested, and the test results are shown in Table 4 below.

[0233] The test method is as follows:

[0234] (1) Water contact angle: The hydrophobicity of the coating was quantitatively tested using an optical contact angle meter. The contact angle (CA) was measured using 5 μL of test liquid. At least three different locations of the same sample were tested and the corresponding average value was taken.

[0235] (2) Surface hardness: Tested in accordance with GB / T 6739-2022.

[0236] (3) 100-grid peel test: Tested in accordance with GB / T9286-1998.

[0237] (4) Wear resistance: Tested according to standard ASTDM D4060.

[0238] (5) Acid and alkali resistance: Tested in accordance with standard GB / T 9274-1988.

[0239] Table 4 Performance test results

[0240]

[0241] Note: The performance test results in Table 4 are the average values ​​of the writing board coatings provided on the surfaces of the three substrates. As an example, the hardness of the writing board coating provided in Example 1 is 10, which represents the average value of the hardness of the writing board coating formed by the coating of the writing board coating provided in Example 1 on the surfaces of SECC, glass and ceramics.

[0242] As can be seen from Table 4, the writing board coating provided in the embodiment of the present application can be strongly attached to metal plates, glass plates, and ceramic plates, thereby increasing the versatility of the coating, and after coating, a coating with high hardness, wear resistance, and corrosion resistance is formed, so that the service life of the coating is significantly increased. In addition, the formed writing board coating has good hydrophobicity, giving the coating excellent easy-to-wipe and easy-to-clean effects. Relative to Comparative Examples 1-2, Example 2 adds microcrystalline cellulose-acrylate modified alkyd resin to the primer coating, which effectively improves the adsorption of the writing board coating to the glass substrate and the ceramic substrate, and combines with other components to form a more uniform and dense coating, so that the wear resistance of the coating is significantly improved. Relative to Comparative Example 3, Example 2 adds titanium dioxide-zirconium dioxide-acrylate polymer to the topcoat coating, which greatly improves the compatibility and bonding of titanium dioxide-zirconium dioxide composite microspheres with other components, and helps to form a writing board coating with good density, so that the hydrophobicity and wear resistance of the coating are significantly improved.

[0243] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A writing board coating, arranged on a writing board body, characterized in that: The coating of the writing board coating includes a primer coating and a top coating; wherein the primer coating includes the following components in the following parts by weight: The topcoat coating comprises the following components in parts by weight:

2. The writing board coating according to claim 1, characterized in that The microcrystalline cellulose-acrylate modified alkyd resin comprises an alkyd resin and microcrystalline cellulose, wherein the alkyd resin and the microcrystalline cellulose are connected via acrylate.

3. The writing board coating according to claim 2, characterized in that The alkyd resin and the acrylate are connected via at least one chemical bond selected from the group consisting of a double bond and a methylene bond; and / or The microcrystalline cellulose and the acrylate are connected via at least one chemical bond selected from the group consisting of a double bond and a carbon-oxygen bond; and / or The mass ratio of the alkyd resin to the microcrystalline cellulose is 23-27:

1.

4. The writing board coating according to claim 2, characterized in that The preparation process of the microcrystalline cellulose-acrylate modified alkyd resin comprises: hydrolyzing the microcrystalline cellulose in a solution system to obtain a cellulose solution; reacting the cellulose solution and methacrylate in a solution system under a first initiator condition to obtain methacrylate-grafted cellulose; mixing butyl acrylate and the alkyd resin, reacting them in a solution system under the condition of a second initiator, to obtain a butyl acrylate modified alkyd resin; The methacrylate grafted cellulose and the butyl acrylate modified alkyd resin are mixed and reacted in a solution system under the condition of a third initiator to obtain the microcrystalline cellulose-acrylate modified alkyd resin.

5. The writing board coating according to claim 1, characterized in that The titanium dioxide-zirconium dioxide-acrylate polymer comprises titanium dioxide-zirconium dioxide composite microspheres and polyacrylate, and the titanium dioxide-zirconium dioxide composite microspheres and the polyacrylate are connected via a silane coupling agent.

6. The writing board coating according to claim 5, characterized in that The titanium dioxide-zirconium dioxide composite microspheres include zirconium dioxide and titanium dioxide deposited on the surface of the zirconium dioxide, and the mass ratio of the zirconium dioxide to the titanium dioxide is 4-6:0.9-1.5; and / or The mass ratio of the polyacrylate to the titanium dioxide-zirconium dioxide composite microspheres is 5-10:4-6.

7. The writing board coating according to claim 5, characterized in that The preparation process of the titanium dioxide-zirconium dioxide-acrylate polymer is as follows: Prepare a first solution containing glacial acetic acid and a second solution containing zirconium dioxide and tetrabutyl titanate; add the second solution into the first solution to react, and then calcine to obtain the titanium dioxide-zirconium dioxide composite microspheres; reacting the titanium dioxide-zirconium dioxide composite microspheres with a silane coupling agent to obtain titanium dioxide-zirconium dioxide composite microspheres modified with the silane coupling agent; The titanium dioxide-zirconium dioxide composite microspheres modified by the silane coupling agent, acrylic monomer and the fourth initiator are reacted in a solution system to obtain the titanium dioxide-zirconium dioxide-acrylate polymer.

8. The writing board coating according to any one of claims 1 to 7, characterized in that: The first epoxy resin and the second epoxy resin independently include at least one of LY1564 epoxy resin and bisphenol A epoxy resin; and / or The first organic solvent and the second organic solvent independently include at least one of n-butyl acetate, isopropyl alcohol, acetone and ethylene glycol methyl ether; and / or The first pigment and the second pigment independently include at least one of calcium carbonate, quartz, barium sulfate and talc; and / or The first film-forming aid and the second film-forming aid independently include at least one of diethylene glycol butyl ether and acrylic acid series film-forming aids; and / or The first leveling agent and the second leveling agent independently include at least one of an acrylic leveling agent and a silicone leveling agent; and / or The first thickener and the second thickener independently comprise associative polyurethane thickeners; and / or The drying agent includes at least one of a cobalt soap drying agent and a manganese soap drying agent.

9. A method for preparing a writing board coating, characterized in that: The following steps are involved: Provide various raw materials according to the coating material of the writing board coating according to any one of claims 1 to 8; The microcrystalline cellulose-acrylate modified alkyd resin, the first epoxy resin, the first pigment, the first organic solvent, the first film-forming aid, the first dispersant, the first leveling agent, the first thickener and the drying agent in the formula of the primer coating are mixed to obtain the primer coating; The titanium dioxide-zirconium dioxide-acrylate polymer, the acrylate, the second epoxy resin, the second pigment, the second organic solvent, the second dispersant, the second film-forming aid, the second leveling agent and the second thickener in the top coating formula are mixed to obtain the top coating; The primer and the topcoat are sequentially coated on the surface of a writing board to form a writing board coating.

10. A writing board, characterized in that: The writing board includes a writing board substrate and a coating disposed on the surface of the writing board substrate, wherein the coating includes the writing board coating according to any one of claims 1 to 8 or the writing board coating prepared by the preparation method according to claim 9.